The future of automated mobilities transition in Aotearoa New Zealand : a thesis presented in fulfilment of the requirements for the degree of Doctor of Philosophy in Resource and Environmental Planning at Massey University, Manawatu, New Zealand. EMBARGOED until 15 October 2026. - Shammut, Moayad (Massey University, 2024)
Automated vehicles (AVs) have been commonly regarded as disruptive technologies of the future with multifaceted implications for cities, economies, and people’s mobilities. However, fundamental to exploiting any benefit from AVs, is the issue of complexity in transitioning towards safer AVs in the future. This research aims to fill this gap in literature and explore the complexity of safer AVs transition in Aotearoa New Zealand (NZ). This research develops a theoretical framework based on the mobilities approach. The mobilities approach explains a wide array of economic, social, political practices and infrastructures that all involve various kinds of movement of people, information, or objects. This framework conceptualises AVs transition through three dimensions of mobilities. First, social mobilities explores how social meanings influence AVs transition. Second, governance mobilities explores how political-institutional factors influence AVs transition. Third, smart mobilities covers how technology risk and readiness influence AVs transition. This research used a qualitative approach by applying the case study of NZ. Data were collected through interviews with government officials and the AVs telecommunication industry, critically reviewing policy and planning documents as well as analysing social media. Firstly, social mobilities involved investigating how safety perceptions, feelings, and cultural practices of society influence AVs adoption. The content analysis of Facebook posts highlighted diversified social meanings for AVs safety, freedom, control and (un)employment that influence AVs adoption. This research found new evidence that developing trust in AVs is influenced by the reputation and achievements of both regulators and developers of technology. The informal driving style of NZ locals requires ‘remarkable competence’ from AVs to negotiate the road safely. NZ society tends to be inclined towards accepting lower-level AVs to maintain the ‘driving pleasure’, and to allow taking vehicle control during safety-critical scenarios. Secondly, governance mobilities involved investigating how political leadership, institutional capacity, and policy discourses steer AVs transition on the basis of their safety. The discourse and thematic analysis of government policy documents and interviews with government officials, revealed how different NZ governments steer AVs policy direction according to their political priorities. This research highlights the complexity of governing AVs due to the involvement of various government organisations with different hierarchical levels, fragmented responsibilities, high interdependencies and conflicting priorities. A strong political leadership coupled with investments for AVs could catalyse a smooth AVs transition. Thirdly, smart mobilities involved focussing on how infrastructure development, hardware, and software influence safe AVs uptake in the future. A focus group discussion and interviews with the AVs industry revealed the necessity for AVs to operate without significant interaction with other road users due to safety risks concerning object classification, GPS positioning, connectivity, and cybersecurity. Findings revealed various potential scenarios for surveillance and exploitation of AV users’ privacy including tracking their mobility habits and data monetisation. NZ roading network requires considerable adjustments to existing (physical and digital) infrastructure. Future infrastructure development may help ease introducing AVs in NZ, especially through developing collaboration between and across tech-industry and the government, to ensure safer uptake of AVs in the future. This research finds that achieving driving autonomy is complex. Transitioning towards safe AVs is dependent on a multitude of different types of factors including social meanings and practices, institutional cultures and norms, strategic visions, political leadership, various public and private sector organisations, technology readiness and enabling infrastructure, as well as influential pioneering actors. This research challenges the traditional technical rhetoric that assumes AVs capable to be deployed ‘everywhere’ and ‘under all conditions’, and rather argues for greater understanding of the complexity of real-life regulatory and urban environments within a specific country context. This research concludes that a successful transition towards safer automated mobility systems will require a holistic understanding of the complexities and interrelationships among the three ‘mobilities’ dimensions, which (each and collectively) significantly influence AVs transition in the future. All in all, the use of the mobilities paradigm in this thesis has been valuable in terms of revealing how the transition towards safer AVs is complex, entangled, heterogenous, and cannot be understood in silos. Existing research on AVs falls short in terms of capturing the complexity of AVs transition from these collective perspectives, hence the contribution of this research to the field. This overall thesis contributes to planning practice in terms of providing insights into a future-focused, long-term, strategic planning for the transition of AVs in NZ. Crucially, this thesis highly recommends the flexibility and openness of planners as AVs transition will occur outside the extant planning processes.
Keywords: automated vehicles; mobilities approach; social meanings; governance; technology disruption; artificial intelligence; Automated vehicles; Social aspects; Government policy; Intelligent transportation systems; Planning; Vehicle-infrastructure integration; New Zealand; 330409 Transport planning